1998
DOI: 10.1111/j.1574-6941.1998.tb00489.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of root exudates and bacterial metabolic activity on conjugal gene transfer in the rhizosphere of a marsh plant

Abstract: Genetic exchange between bacteria in natural habitats is believed to be strongly influenced by availability of growth substrates and growth rate. To test this hypothesis, conjugal transfer of an RP4 derivative between Pseudomonas fluorescens and Serratia sp. was studied in a simple sand/plant microcosm and was related to availability of root exudates and bacterial metabolic activity. The presence of the plant (Echinochlora crusgalli) greatly stimulated transfer. Average transfer ratios (T/ DWR) were 8.9U10 3II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 25 publications
(38 reference statements)
0
32
1
Order By: Relevance
“…In addition to its crucial role in the nodulation process, it was shown to stimulate wheat and Arabidopsis thaliana colonization by A. caulinodans (29,30). It was previously reported that opines produced by crown gall tumors initiated on plants by the pathogen Agrobacterium tumefaciens are required for Ti plasmid conjugal transfer among agrobacteria (31) and that root exudates enhance bacterial conjugal gene transfer in the rhizosphere (32,33). Our findings provide another example of the role of the host in the transfer of bacterial functions involved in interactions with eukaryotes, including bacteria-animal associations (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its crucial role in the nodulation process, it was shown to stimulate wheat and Arabidopsis thaliana colonization by A. caulinodans (29,30). It was previously reported that opines produced by crown gall tumors initiated on plants by the pathogen Agrobacterium tumefaciens are required for Ti plasmid conjugal transfer among agrobacteria (31) and that root exudates enhance bacterial conjugal gene transfer in the rhizosphere (32,33). Our findings provide another example of the role of the host in the transfer of bacterial functions involved in interactions with eukaryotes, including bacteria-animal associations (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…In roots, root nodules, and guts, lateral transfer of genetic material between different bacteria has been evidenced (2,162,163), seemingly promoted by close contacts in high-density populations. The presence of similar catabolic or antibiotic resistance genes in various gut bacterial genera has been explained as acquisitions by lateral gene transfers (91).…”
Section: Evolutionary Pathwaysmentioning
confidence: 99%
“…virulence, antibiotic resistance, etc.) has been demonstrated in roots 38) and leaves 50) of plants growing in controlled and field conditions. Finally, aggregation itself may promote the survival of bacteria by protecting the individual cells from various chemical and physical stresses.…”
Section: Biofilms Found In Association With Plantsmentioning
confidence: 99%